Multi-temporary analysis of the lagoon Suches and vegetation vigor of peatland Huaytire, Tacna - Chambe Bahamontes, José Francisco (2021)
The lagoon Suches and the peatland Huaytire, located in the province of Candarave in the department of Tacna, are important ecosystems that provide various ecosystem services. In this research, the change in the area of the water mirror of the lagoon Suches and the change in the NDVI values of the peatland Huaytire between 1975 and 2020 were determined by analyzing satellite images obtained from the United States Geological Survey - USGS (Landsat 2, Landsat 5, Landsat 7 and Landsat 8). The Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI) were calculated. The results show a notable decrease in the area of the Suches lagoon and in the vegetation vigor, the latter indicating a decrease in the cover of the peatland Huaytire. Although it was not possible to establish a causal relationship with the factors causing this decrease, the scientific evidence reviewed suggests that climate change, surface and groundwater diversion and extraction, as well as camelid livestock grazing, would be responsible for the results found.